THE APPLICATION OF NANOTECHNOLOGY FOR MICRONUTRIENT IN AGRICULTUREAL PRODUCTION (REVIEW ARTICLE) - & Al-Juthery, Ali (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
Micronutrients can be considered as one of the main component for high and good quality agricultural products and human health.  Many Researchers and Scientists around the world indicated that more than 3 billion person around the world affected by shortage in micronutrients especially Fe and Zn .This problem cannot be solved through food additives at developing poor countries and Biofortification is the only answer through naturally enriched agricultural products with micronutrients.  Micronutrients can limit food quality and quantity in spite of the low amounts required by crops compared to macronutrients. Micronutrient are available in different formulas and structures as mineral ,synthetic chelated and organic fertilizers and can be applied either to soil or as foliar or mixed of both .However ,  fertilizer use efficiency (FUE) or nutrients recovery by plants still 5%. Recently the use of nanotechnology for micronutrients in agricultural production being adopted and hope this technology will have an important part in solving the low recovery but the issue at its outsets and still in the need of further understanding ,investigations' and financial support.